Assessing the influence of treating therapist and patient prognostic factors on recovery from axial pain. (1st November 2013) - Simon, Corey B; Stryker, Sandra E; George, Steven Z
<x xml:space="preserve">Abstract</x> Background: Limited research exists regarding the influence of a treating physical therapist on patient recovery (deemed therapist effects). Recent randomized clinical trials data provide an indication of small therapist effects for manual therapy; however, the extent to which therapist effects exist in the average outpatient facility is not clear. Moreover, patient-related prognostic factors, like fear-avoidance or pain duration, are important to consider since these may also influence the extent of therapist effects. Objective: To assess therapist effects and the influence of patient prognostic factors on recovery from axial pain in an outpatient orthopedic physical therapy facility. Methods: Clinical data were collected from consecutive patients with musculoskeletal neck and low back pain. Patient outcomes included pain intensity (visual analog scale) and functional measure (CareConnections functional outcomes index) scores. Therapist effects estimates and the influence of intake fear-avoidance (fear-avoidance beliefs questionnaire) and pain duration (days) were examined using multilevel linear or regression modeling. Results: A total of 258 patients (160 females; mean age 46·4±14·9 years) completed physical therapy and the required outcome measures. Five physical therapists (1-13 years of experience, mean 5·8 years) provided treatment. Therapists effects did not exist for discharge pain intensity or function after accounting for intake scores (P > 0·05). Further, therapist experience did not influence patient outcomes. Patient prognostic factors of fear-avoidance and pain duration did not influence therapists effects on the same patient outcome measures (P > 0·05). Discussion: Preliminary findings suggest that there are no major differences in patient outcome based on either the individual therapist (therapist effect) or therapist experience in this type of PT setting. Established prognostic factors had no influence on therapist effects for this cohort. Future analyses should consider intrinsic therapist factors (beliefs, equipoise), specific treatment parameters (dosage, type), and other patient prognostic factors (psychological, age, expectation, satisfaction) to further elucidate the influence of therapist effects.